Macroeconomic effects of unconventional monetary policy in the euro area - Gert Peersman (European Central Bank (ECB), 2011)
I find that the Eurosystem can stimulate the economy beyond the policy rate by increasing the size of its balance sheet or the monetary base. The transmission mechanism turns out to be different compared to traditional interest rate innovations: (i) whilst the effects on economic activity and consumer prices reach a peak after about one year for an interest rate innovation, this is more than six months later for a shift in the monetary base that is orthogonal to the policy rate (ii) interest rate spreads charged by banks decline persistently after a rise in the monetary base, whereas the spreads increase significantly after a fall in the policy rate (iii) there is no significant short-run liquidity effect after an interest rate innovation, that is additional bank loans are generated by a greater credit multiplier. In contrast, the multiplier declines considerably after an expansion of the Eurosystem's balance sheet.
Keywords: C32; E30; E44; E51; E52; 330; SVARs; Unconventional monetary policy; Geldpolitik; Zinspolitik; Finanzprodukt; Wirkungsanalyse; Eurozone